The Analysis of Students’ Difficulties in Solving Systems of Linear Equation Problems in Two Variables - Ernawati Ernawati; Muhammad Muzaini (Jurnal Studi Guru dan Pembelajaran, 2020)
This study aimed to determine the difficulties experienced by students and the factors that cause students to experience difficulties in solving questions related to systems of linear equation in two variables (SPLDV). This study used a qualitative approach by applying the descriptive research. The subjects in this study were students of class IX1 at SMP Negeri 1 Bontomarannu. Data collection techniques used diagnostic test material of systems of linear equation in two variables and interviews. Data analysis techniques used qualitative data analysis consisted of data reduction, data presentation and drawing conclusion. The results revealed that: (1) Difficulties experienced by students of class IX1 at SMP Negeri 1 Bontomarannu in solving questions regarding to systems of linear equation in two variables consisted of the first is the concept difficulty which lies in the students' mistakes in giving reasons whether it is systems of linear equation in two variables or not, the students cannot determine the variables in a system of linear equation in two variables, errors in writing the set of resolutions and students do not understand the notion of the combined method of solving systems of linear equation in two variables. The second is the difficulty of principle; it lies in errors in changing into standard form, mistakes in changing an equation and errors in using formulas in general in the completion of the combined method. The third is the difficulty of the skill, which lies in errors in writing the standard form, errors and difficulties in operating numbers and student errors in writing questions when completing answers. (2) Factors that cause students to experience difficulties in completing systems of linear equation in two variables questions consisted of having no interest in learning material in mathematics, having a lack of ability to acquire, understand and solve systems of linear equation problems in two variables, families do not provide motivation to students to be more active in learning, lack of learning routines, they could not calculate correctly.